2007
DOI: 10.1111/j.1365-2133.2007.08039.x
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of peripheral blood mononuclear cells and CD4+ T cells from patients with psoriasis to cultured endothelial cells via the interaction between lymphocyte function-associated antigen type 1 and intercellular adhesion molecule 1

Abstract: These findings indicate that the LFA-1/ICAM-1 interaction plays a major role in the adhesion of CD4+ T cells to endothelial cells and that TNF-alpha might play an important role for the induction of adhesion molecules on endothelial cells at psoriatic skin lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
(98 reference statements)
2
13
0
1
Order By: Relevance
“…Previous studies have demonstrated that HMVECs have increased expression of select adhesion molecules induced by TNFα [28]. Cell surface ELISAs were performed to determine TNFα (25 ng/ml)-induced endothelial molecules implicated in angiogenesis - namely VCAM-1, ICAM-1, E-selectin, and JAM expression on HMVECs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that HMVECs have increased expression of select adhesion molecules induced by TNFα [28]. Cell surface ELISAs were performed to determine TNFα (25 ng/ml)-induced endothelial molecules implicated in angiogenesis - namely VCAM-1, ICAM-1, E-selectin, and JAM expression on HMVECs.…”
Section: Resultsmentioning
confidence: 99%
“…Research demonstrates that the adhesion of CD4+ T cells to endothelial cells and the resulting migration to skin tissue are necessary in the development of psoriatic skin lesions. The adhesion molecules lymphocyte function associated antigen (LFA-1 or CD18) and ICAM-1 are key in the adhesion of CD4+ T cells to the endothelial wall (Watabe et al, 2007). Currently, both cell adhesion molecule antagonists and cytokine antagonists are approved for the treatment of psoriasis (Berger and Gottlieb, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, in some pathological conditions, such as in the inflammatory process, leukocyte accumulation can be amplified rapidly, which is an important pathogenic factor in tissue damage and the development of many types of pathologic inflammatory disorders, including inflammatory skin diseases (Charo and Ransohoff 2006). Human dermal microvascular endothelial cells, known as a selective barrier between the circulating blood and the vessel wall, are responsible for leukocyte migration into inflamed skin by the expression and secretion of adhesion molecules and chemokines (Swerlick and Lawley 1993;Watabe et al 2007). …”
Section: Introductionmentioning
confidence: 98%